Hubungan gender dengan strategi pembelajaran bahasa Arab dalam kalangan pelajar sekolah menengah agama di Terengganu - Mat Teh, Kamarul Shukri; Nik Yusoff, Nik Mohd Rahimi; Embi, Mohamed Amin; Mahamod, Zamri (UUM College of Arts and Sciences, 2008)
Female students have reported that they use Language Learning Strategies (LLS) more often than male students in many studies across different cultures (Ehrman & Oxford, 1989; Green & Oxford, 1995). However, some studies have demonstrated no statistically significant difference between gender in the use of LLS(Chang, 1990; Chou, 2002). Yet others have shown that male students use more LLS than female students in certain strategy categories(Oxford, 1994; Wharton, 2000). Linguistics differences are also known to influence strategy use (Douglas, 1992; Grabe, 1986). This paper describes the LLS employed by students of Arabic language based on gender. The subjects comprised 460 Form 4 students from 13 religious secondary schools in Terengganu. Data were collected using an Arabic language learning strategy questionnaire adapted and modified from SILL (Oxford, 1990). The results of the study indicate that overall, female students of Arabic language tended to use LLS more frequently than male students. The result also showed that female students use more LLS than male students in the following three categories: memory, affective and metaphysical. However, no statistically significant differences were found in the use of cognitive, metacognitive, compensation and social strategies.